Efecto de horas luz en productividad de ponedoras Hy Line, periodo Invierno – Verano, en inversiones El Tablazo S.A.C en Huanchaco - Vasquez Alva, Alexandra Antonella (2019)
This research work was carried out at the Farm Inversiones El Tablazo S.A.C., located in the district of Huanchaco, with the purpose of determining the effect of light hours on productivity of Hy Line layers, winter - summer period; Likewise, identify to what extent it is greater in one season or in the other and evaluate the productive indices. 378 laying hens of the Hy Line line were used, divided into two treatments; T1 (summer) and T2 (winter). The results were analyzed using descriptive statistics, obtaining the following results: in the percentage of production: T1 ( 79.13%) and T2 (64.93 %),in the food conversion: T1 (0.65 kg ) and T2 (1.38 kg), in the weight of the egg: T1 (55.58 gr) and T2 (58.60 gr), in the weight of the birds: T1 (1832.38 gr) and T2 (1841.93 gr), in mortality: T1 (0.19%) and t2 (0.09), the age of the production peak: T1 (24 weeks; 95.81%) and T2 (32weeks; 95.81%), in food consumption: T1 (113.42 gr / bird / day) and T2 (108.62 gr / bird / day), the number of accumulated egg / bird / day: T1 (84.05) and T2 (37.45), the number of ac-cumulated egg / poultry egg: T1 (80.22) and T2 (35.15) and the Egg mass: T1 (44.56kg) and T2 (39.75g kg). It is concluded that by having more daylight hours in the summer sea-son, the percentage of productivity in Hy Line layers increased, higher than in the winter season.